COMMUNICATIVE COMPETENCE IN A GLOBAL HOSPITALITY WORKPLACE: ASSESSMENT OF ENGLISH LANGUAGE COMPETENCY OF BSHM GRADUATING STUDENTS - Arriane Kris M. Manalastas (SEAMEO QITEP in Language, 2023)
This paper aimed to determine the 76 Bachelor of Science in Hospitality Management (BSHM) graduating students’ self- assessed English language communicative competence, their English language competency level and the factors that have contributed to their English competency using the Descriptive- Correlational Research Design and Thematic Analysis through a survey questionnaire, teacher- made test, and open- ended questionnaire. The result showed that the graduating students have evaluated themselves as competent in their overall competency in the English language, the students demonstrated a high level of communicative competence, and there is no significant association with their self-assessed competency and their actual competence in the English language because there might be factors other than self- perceived competency that were contributing to the level of English proficiency of students. In addition, affective factors such as anxiety, self- confidence, and motivation, cognitive factors such as semantic familiarity, and their growing and learning environment and prior linguistic knowledge and exposure had influenced the students’ English competency. It was suggested that a training program in English to develop the self- confidence and motivation and reduce the student’s anxiety in using English, promotion of communicative language teaching and creating of enabling environment for the usage of the language in classes should be conducted, and an actual speaking and writing skills test should be administered.